2020
DOI: 10.1002/art.41184
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Synovitis and Clinical Phenotypes in Rheumatoid Arthritis: Relationship to Disease Stages and Drug Exposure

Abstract: and the PEAC-R4RA Investigators Objective. To define the relationship of synovial B cells to clinical phenotypes at different stages of disease evolution and drug exposure in rheumatoid arthritis (RA).Methods. Synovial biopsy specimens and demographic and clinical data were collected from 2 RA cohorts (n = 329), one of patients with untreated early RA (n = 165) and one of patients with established RA with an inadequate response to tumor necrosis factor inhibitors (TNFi-IR; n = 164). Synovial tissue was subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 47 publications
0
35
1
Order By: Relevance
“…CD20 staining was evaluated at three cutting levels on a minimum of six biopsies, which is recommended for use in clinical trials and reported to be representative of the whole joint tissue. 27 Although the semi-quantitative score used for balanced stratification (before randomisation) had been validated both against digital image analysis and the transcript concentrations, determined using the FANTOM5-derived B-cell related gene set, 20 , 25 because no published gold standard is available, the cutoff of 0–1 for B-cell poor classification and 2–4 for B-cell rich classification was set arbitrarily on the basis of a previous pilot study and might not have been at an optimal level for the whole trial. Furthermore, considering that these cutoffs were determined by physically counting the number of CD20 B cells, miscounting had the potential for misclassification.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CD20 staining was evaluated at three cutting levels on a minimum of six biopsies, which is recommended for use in clinical trials and reported to be representative of the whole joint tissue. 27 Although the semi-quantitative score used for balanced stratification (before randomisation) had been validated both against digital image analysis and the transcript concentrations, determined using the FANTOM5-derived B-cell related gene set, 20 , 25 because no published gold standard is available, the cutoff of 0–1 for B-cell poor classification and 2–4 for B-cell rich classification was set arbitrarily on the basis of a previous pilot study and might not have been at an optimal level for the whole trial. Furthermore, considering that these cutoffs were determined by physically counting the number of CD20 B cells, miscounting had the potential for misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were then stained for haematoxylin and eosin and immune-histochemical markers ( appendix p 13 ), as previously described. 3 , 20 Sections underwent semi-quantitative scoring to determine expression of CD20 B cells, CD3 T cells, CD138 plasma cells, and CD68 lining and sublining macrophages ( appendix p 13 ). The scoring process was adapted from a previously described and validated score.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Synovial sections underwent standard H&E staining and semi-quantitative (SQ) assessment of synovitis according to a previously validated score (Krenn) ( Krenn et al., 2006 ). Sequentially cut sections underwent Immunohistochemical (IHC) staining and upon SQ scoring (0‑4), sections were stratified into synovial pathotypes according to the degree of immune cell infiltration: i) Lymphoid- grade 2/3 B cell aggregates, CD20≥ 2 and/or CD138>2, ii) Myeloid- CD68 SL≥ 2, CD20 ≤ 1 and/or CD3≥1, CD138 ≤ 2, and iii) Fibroid- CD68 SL<2 and CD3, CD20, CD138<1) ( Humby et al., 2009 ; Rivellese et al., 2019a ). Following IHC staining for CD117, patients were classified as MC+/MC-, based on the presence/absence of synovial mast cells and MC density (n of cells/mm 2 ) was calculated by automated cell counting (cellSens, Olympus).…”
Section: Methodsmentioning
confidence: 99%